Role of vertical jumps and anthropometric variables in maximal kicking ball velocities in elite soccer players - Rodriguez-Lorenzo, L.; Fernandez-del-Olmo, M.; Sanchez-Molina, J. A.; Martin-Acero, R. (Journal of Human Kinetics, 2016)
Kicking is one of the most important skills in soccer and the ability to achieve ma ximal kicking velocity with both legs leads to an advantage for the soccer player. This study examined the relationship be tween kicking ball velocity with both legs using anthropometric measurements and vertical jumps (a squat jump (SJ); a countermovement jump without (CMJ) and with the arm swing (CMJA) and a reactive jump (RJ)). Anthropome tric measurements did not correlate with kicking ball velocity. Vertical jumps correlated significantly with kicking ball velocity using the dominant leg only (r = .47, r = .58, r = .44, r = .51, for SJ, CMJ, CMJA and RJ, respectively) . Maximal kicking velocity with the dominant leg was significantly higher than with the non-dominant leg (t = 18.0 4, p < 0.001). Our results suggest that vertical jumps may be an optimal test to assess neuromuscular skills involved in kicking at maximal speed. Lack of the relationship between vertical jumps and kicking velocity with the non-dominant leg may reflect a difficulty to exhibit the neuromuscular skills during dominant leg kicking.